2017
DOI: 10.1158/1078-0432.ccr-16-0914
|View full text |Cite
|
Sign up to set email alerts
|

Bromodomain and Extraterminal Protein Inhibitor JQ1 Suppresses Thyroid Tumor Growth in a Mouse Model

Abstract: Purpose New therapeutic approaches are needed for patients with thyroid cancer refractory to radioiodine treatment. An inhibitor of bromodomain and extraterminal domain (BET) proteins, JQ1, shows potent anti-tumor effects in hematological cancers and solid tumors. To evaluate whether JQ1 is effective against thyroid cancer, we examined anti-tumor efficacy of JQ1 using the ThrbPV/PVKrasG12D mouse, a model of anaplastic thyroid cancer. Experimental Design We treated ThrbPV/PVKrasG12D mice with vehicle or JQ1 a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 51 publications
(62 reference statements)
1
45
1
Order By: Relevance
“…Aberrant up-regulation of any MYC family member (MYC, MYCN, or MYCL) promotes metabolic reprograming that leads to sustained proliferation of cancer cells (Brodeur et al 1984;Nau et al 1985;Hatton et al 1996;Beroukhim et al 2010;Liu et al 2012;Hsieh et al 2015). Because MYC is a universal oncogene, there have been several attempts to develop inhibitors that block MYC functions specifically in tumors (Soucek et al 1998;Filippakopoulos et al 2010;Hurlin 2013;Hart et al 2014;McKeown and Bradner 2014;Abedin et al 2016;Alghamdi et al 2016;Zhu et al 2017). However, MYC is still considered an undruggable protein (McKeown and Bradner 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant up-regulation of any MYC family member (MYC, MYCN, or MYCL) promotes metabolic reprograming that leads to sustained proliferation of cancer cells (Brodeur et al 1984;Nau et al 1985;Hatton et al 1996;Beroukhim et al 2010;Liu et al 2012;Hsieh et al 2015). Because MYC is a universal oncogene, there have been several attempts to develop inhibitors that block MYC functions specifically in tumors (Soucek et al 1998;Filippakopoulos et al 2010;Hurlin 2013;Hart et al 2014;McKeown and Bradner 2014;Abedin et al 2016;Alghamdi et al 2016;Zhu et al 2017). However, MYC is still considered an undruggable protein (McKeown and Bradner 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Bromodomain and extraterminal domain (BET)‐family proteins, which include BRD2, BRD3, BRD4 and BRDT, are epigenetic reader proteins that bind to acetylated‐lysine residues on histones and promote gene transcription by interacting with positive transcription elongation factor b (P‐TEFb) and RNA polymerase II . BET inhibitors bind to BET proteins’ (predominantly BRD4's) recognition pocket for acetylated‐lysine residues and thereby inhibit BET‐histone binding and recruitment of transcriptional complexes to genomic loci, and the results of preclinical studies have indicated that BET inhibitors are broadly active in different cancer types, including NSCLC . Although the effect of BET inhibitors on the expression of oncogenes such as c‐Myc has been extensively addressed, the mechanisms by which BET inhibition produces cytotoxicity remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] BET inhibitors bind to BET proteins' (predominantly BRD4's) recognition pocket for acetylated-lysine residues and thereby inhibit BET-histone binding and recruitment of transcriptional complexes to genomic loci, 6,7 and the results of preclinical studies have indicated that BET inhibitors are broadly active in different cancer types, including NSCLC. [8][9][10][11][12][13] Although the effect of BET inhibitors on the expression of oncogenes such as c-Myc has been extensively addressed, 10,14 the mechanisms by which BET inhibition produces cytotoxicity remain unknown. However, several recent studies have reported that BRD4 is essential for the repair of DNA double-strand breaks (DSBs), and that BET inhibitors suppress both of the major DSB repair mechanisms, homologous recombination (HR) and nonhomologous end joining (NHEJ).…”
Section: Introductionmentioning
confidence: 99%
“…BRD4 inhibitors that displace the BET bromodomain from chromatin also have progressed in preclinical models. In thyroid cancer, mouse anaplastic thyroid cancer models are sensitive to BRD4 inhibition and show reduced tumor burden and suppression of MYC expression (43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%